The Role of Customer Service in Establishing Trust in Fintech through ShopeePay on the Shopee Platform - Hamidah, Hamidah; Oktaviani, Sagita Dela; Sianturi, Ezra Riyanti; Adela Putra, Billy Rifallo; Abraham Jansen, Warouw Vallencio; Susilawati Sugiana, Neng Susi (INSTITUT DIGITAL EKONOMI LPKIA, 2025)
This study aims to explore the role of customer service in building user trust in fintech services, specifically ShopeePay on the Shopee platform. With the rapid rise of digital payment systems, trust has become a critical factor influencing user adoption and continued usage. Using a qualitative research method, in-depth interviews were conducted with 50 ShopeePay users to gather insights into their experiences with customer service and its impact on their trust in the platform. The results indicate that responsive, empathetic, and solution-oriented customer service significantly contributes to fostering trust in ShopeePay. Users emphasized the importance of clear communication, timely problem resolution, and a sense of security when interacting with customer service representatives. Practical implications suggest that improving service quality and user experience through customer service strategies can enhance customer loyalty and strengthen brand credibility in the fintech ecosystem. The findings underscore the strategic role of customer service as not only a support function but also a trust-building mechanism in digital financial services.